Trastorno antisocial de la personalidad que presentan los internos de 18 a 30 años de edad del Centro de Rehabilitación Social de la ciudad de Machala. - Guamán Orrala, Nilda Magaly (2014)
In the first instance it is important to mention that the environment in which the individual and its relations with other lives influences the formation of his personality. The personality is thus a biopsychosocial nature, is the sum of different elements that influence to originate, and constituted complex form, that global picture that characterizes each man as unique.